Can growth opportunities explain the diversification discount? - Stowe, John D.; Xing, Xuejing (Journal of Corporate Finance, 2006)
We investigate the possibility that the diversification discount is due to differing growth opportunities between diversified and single-segment firms. We do this by comparing diversified business segments with individual single-segment same-industry firms of comparable growth opportunities. Using a sample of 230 diversifying firms from 1981 to 1997, we find a significant valuation discount in diversified firms even when we control for the difference in growth opportunities between diversified and single-segment firms. This result suggests that differing growth opportunities between diversified and single-segment firms cannot account for the diversification discount.